Making Details Matter: How to Reform Aid Agencies to Generate Contextual Knowledge - and Ang, Yuen Yuen (SSRN, 2014)
My essay considers a central problem of reinventing foreign aid in the twenty-first century: how to reform aid agencies to enable a “best-fit” approach to development assistance. For the past decades, the aid community has tried to transplant best practices from the developed world to the developing world. Increasingly, however, it is recognized that copying best practices does not work and may even backfire; rather, aid programs work best when they are tailored to local contexts. Yet while the idea of a best-fit approach is widely embraced in principle, actualizing it is easier said than done. For meaningful changes to take root in practice, we must first identify the obstacles to localizing development assistance and suggest ways to address these problems. To this end, I propose a three-pronged strategy to promote the generation of contextual knowledge among aid professionals, a necessary condition for crafting solutions that can fit various local contexts, namely: (1) build a bank of knowledge about unorthodox practices that work, (2) diversify expertise within aid agencies; and (3) carve experimental pockets. My proposal does not fit neatly into any one of the six themes specified in the GDN competition; rather, it concerns all of the themes. Whether it is to use aid to improve governance, apply information technology, or design financial instruments, the overarching challenge is to empower and incentivize aid professionals to learn and apply contextual knowledge to creatively solve problems in developing societies.
Keywords: Contextual knowledge; Localization; Public policy; foreign aid; international development